(3GdJMcje GdJLGQj GdOhdj (B:s (3OQGSI ebGQfI dCMcGe GdJMcje GdJLGQj GdOhdj ceG LGFJ aj GdbhGYO hGdGJaGbjGJ GdOhdjI hGdEbdjejI hGdYQHjI eY ETGQI Edi CMcGe GdJMcje aj GdJTQjYGJ GdYQHjI (B= The international Commercial Aebitration A Comparative Study Of The provisions OF The international Commercial Arbitration : As Stipulated In The Rule and international Regional and Arabian Coventions With Referring To THE Arbitration Provisions The Arabic Legislations /s - (3SGej, ahRj eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2015)
(3aj gPG GdcJGH OQGSI ebGQfI dCMcGe GdJMcje GdJLGQj GdOhdj ceG LGAJ aj GdbhGYO hGdGJaGbjGJ GdOhdjI hGdEbdjejI hGdYQHjI eY ETGQI Edi CMcGe GdJMcje aj GdJTQjYGJ GdYQHjI, aj GdHOGjI YQaJ GdOQGSI HCgejI GdJMcje ef NdGd GdGJaGbjGJ GdOhdjI hGdEbdjejI GdYQHjI hGdCLfHjI GdJj YbOJ aj gPG GdeLGd, Ke OQSJ CMcGe GdJMcje efP GJaGb GdWQajf GdeJYGbOjf Ydi GJHGYg dMSGe NdGaGJge, dMjf EUOGQ GdbQGQ GdJMcjej hJfajPg Ch GdWYf ajg, hde JbJUQ Ydi CMcGe GdJMcje GdJLGQj GdOhdj, Hd TedJ GdJMcje HhLg YGe, hPdc dCf GdJMcje GdOhdj bO jNVY dCMcGe GdbGfhf GdeMdj ShGA CcGf Pdc HGdfSHI ddELQGAGJ Ch HGdfSHI ddbGfhf GdPj jWHb Ydi ehVhY GdfRGY(B. (3ceG Cf JfajP GdbQGQ GdJMcjej jNVY aj GdZGdH ddbhGYO GdELQGFjI dbGfhf GdHdO GdeQGO JfajP GdbQGQ ajg(B.s
(3HHdjhLQGajI (B: (3UaMI (B453-470.s
Keywords: (3GdJMcje GdJLGQj GdOhdjs; (3GdJMcje GdJLGQjs